Avaliação in vitro da atividade antifúngica da Malpighia glabra linn. em agentes da cromoblastomicose - CRUZ, Naila Ferreira da (Universidade Federal do Pará, 2017)
Chromoblastomycosis (CBM) is a mycosis by implantation, chronic, with a cosmopolitan distribution, caused by melanized fungi. After transcutaneous implantation, the propagules of the CBM agents present a unique cellular and morphological plasticity. The cellular differentiation results in the appearance of muriform cells. The treatment of this mycosis is a challenge due to the absence of a standard antifungal, resulting in several therapy methods (physical and pharmacological), used isolated or associated, with little clinical cure success. Amazon region has a vast biodiversity of vegetables that need to be better characterized as to their chemical composition and applicability in the treatment of different diseases. In this variety of plants, the fruit of Malpighia glabra Linn. (acerola) has a high content of vitamin C, also presenting vitamins of the complex B, A, anthocyanins and flavonoids, which stand out for having different biological and therapeutic actions already demonstrated both in vitro and in vivo. A major interest is currently focused on the biological activities of quercetin, belonging to the class of flavonoids, as it exerts multiple pharmacological activities, presenting unique biological properties that can improve mental and/or physical performance and reduce the risk of different infections. This study aims to evaluate the in vitro antifungal activity of M. glabra extract in conidia and muriform cells of Fonsecaea spp. The extract of M. glabra presented antifungal activity in both, conidia and muriform cells, of the evaluated strains. Much interest is now centered on biological activities of the flavonoid quercetin. In addition to the crude extract, the conidia of different strains were also sensitive to different dilutions of the extract. The minimum inhibitory concentration (MIC) and the minimum fungicidal concentration (MFC) were evaluated. The geometric mean of the quercetin MIC for the conidia was 4.75 μg/mL and the geometric mean of the CFM was 11.31 μg/mL. Further study is needed so that M. glabra or quercetin, isolated or associated with another isolated component of the extract, may be used for the treatment of CBM in the future.